2021
DOI: 10.1108/wje-10-2020-0529
|View full text |Cite
|
Sign up to set email alerts
|

Detection of COVID-19 cases through X-ray images using hybrid deep neural network

Abstract: Purpose The latest 2019 coronavirus (COVID-2019), which first appeared in December 2019 in Wuhan's city in China, rapidly spread around the world and became a pandemic. It has had a devastating impact on daily lives, the public's health and the global economy. The positive cases must be identified as soon as possible to avoid further dissemination of this disease and swift care of patients affected. The need for supportive diagnostic instruments increased, as no specific automated toolkits are available. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Diao et al [20] has shown the effect of COVID-19 on the kidney and acute renal failure. Nair et al [21] have built a CNN model on more levels and modified its internal parameters for a specific task such as classification or recognizing objects. There is a typical CNN structure with an extract filter from the input by a convolution layer.…”
Section: Background Studymentioning
confidence: 99%
“…Diao et al [20] has shown the effect of COVID-19 on the kidney and acute renal failure. Nair et al [21] have built a CNN model on more levels and modified its internal parameters for a specific task such as classification or recognizing objects. There is a typical CNN structure with an extract filter from the input by a convolution layer.…”
Section: Background Studymentioning
confidence: 99%
“…This puts government officials in unexpected situations. Non-pharmaceutical interventions, like the use of effective face masks, the closure of educational institutions, the restriction of travel, and stringent containment measures, have the most significant interventions for flattening the Epidemic Curve [3] . Furthermore, mass testing and tracking are also essential if the continuous transmission chain is to be broken.…”
Section: Introductionmentioning
confidence: 99%
“…That lack of interest encourages people to take impulsive act, forcing government ministers in new situations. Non-pharmaceutical interventions with effective face covering, the lockdown of academic institutions, restricted transportation, and additional security are the most powerful interventional tactics to smooth the Pandemic Slope [3] , [4] , [5] . This concludes that if the continuous transmission chain is to be disrupted, then widespread testing and tracking are required.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, neural networks gained excessive achievements in the field of medical imaging, due to their self-learning capabilities and high aptitude for automatic feature extraction [16]. Especially, deep neural networks can distinguish infectious and virusrelated pneumonia for chest radiographs [17][18][19][20][21]. Therefore, in this article, we introduce a hybrid deep neural network (HDDNs) for the diagnosis of COVID-19, using CT and X-ray images.…”
Section: Introductionmentioning
confidence: 99%